The relationship between TEC and Earth's magnetic field during quiet and disturbed days over Istanbul, Turkey - Ozcan, O.; Sagir, S.; Atici, R. (Elsevier Sci Ltd, 2020)
In this study, the impact of Earth's magnetic field on total electron content (TEC) was studied by using statistical multiple linear regression model and co-integration method. TEC values were measured over the Turkey-Istanbul (ista) station using date of global positioning system (GPS), and the magnetic field components of the Earth were measured from Bogazici University, Kandilli Observatory and Earthquake Research Institute, Geomagnetic observatory Istanbul (ISK) station. This examination has been carried out during the dates of March 14-19, 2015 covering the dates of March 17-18, 2015 known in the literature as St. Patrick's Day geomagnetic storm. The three days before the storm (March 14-16) were named as quiet days, whereas the other days (March 17-19) were named as disturbed days after which the two periods were examined separately. It was observed as a result of the examination that the x-component (south-north direction) of the magnetic field had a negative impact on TEC on quiet days, whereas the impact was positive on disturbed days. However, the y-component (east-west direction) of the magnetic field had an inverse relationship of the x-component on the quiet and disturbed days. In addition, it was deduced that the impact coefficient of the x and y-component of the magnetic field was higher on disturbed days in comparison with those on quiet days. The correlation coefficient between the TEC and the components of the Earth's magnetic field was 0.11 on quiet days and 0.95 on disturbed days. Therefore, it can be stated that the relationship of the TEC values with the geomagnetic field are higher on disturbed days. (C) 2020 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Earth's magnetic held; Ionospheric TEC; Multiple linear regression model